A usability and safety analysis of electronic health records: a multi-center study. (2nd July 2018) - Ratwani, Raj M; Savage, Erica; Will, Amy; Arnold, Ryan; Khairat, Saif; Miller, Kristen; Fairbanks, Rollin J; Hodgkins, Michael; Hettinger, A Zachary
Abstract: To characterize the variability in usability and safety of EHRs from two vendors across four healthcare systems (2 Epic and 2 Cerner). Twelve to 15 emergency medicine physicians participated from each site and completed six clinical scenarios. Keystroke, mouse click, and video data were collected. From the six scenarios, two diagnostic imaging, laboratory, and medication tasks were analyzed. There was wide variability in task completion time, clicks, and error rates. For certain tasks, there were an average of a nine-fold difference in time and eight-fold difference in clicks. Error rates varied by task (X-ray 16.7% to 25%, MRI: 0 to 10%, Lactate: 0% to 14.3%, Tylenol: 0 to 30%; Taper: 16.7% to 50%). The variability in time, clicks, and error rates highlights the need for improved implementation optimization. EHR implementation, in addition to vendor design and development, is critical to usable and safe products.